Aproximación a la distribución de la industria de servicios informáticos en España - Escolano Utrilla, Severino (Geographicalia, 2017)
The recient explosion of the number and the geographic dispersion of the Computing Service Industry in Spain (ISI) has been accompanied of continuons processes of restructuring of the territorial relations of production of jobs among the enterprises by virtue of their localization, toward the polarization and fork according to the business size, at the same time as in the bosom of the ISI organizational and functional readjustments are mude, wich has an effect on the training of the workers.